Involvement of AsA/DHA and GSH/GSSG Ratios in Gene and Protein Expression and in the Activation of Defence Mechanisms Under Abiotic Stress Conditions - Fotopoulos, Vasileios; Ziogas, Vasileios; Tanou, Georgia; Molassiotis, Athanassios (My University, 2010)
In a persistently changing environment there are many adverse abiotic stress conditions such as cold, heat, drought, salinity, heavy metal toxicity and oxygen deprivation, which remarkably influence plant growth and crop production. Plant cells produce oxygen radicals and their derivatives, so-called reactive oxygen species (ROS) during various processes associated with abiotic stress. Moreover, the generation of ROS is the main means for higher plants to transmit cellular signalling information concerning the changing environmental conditions. Therefore, plants have evolved inducible redox state-based sensing mechanisms that are activated or amplified in response to adverse environmental conditions. Ascorbate and glutathione, the key cellular redox buffers, are used for both detoxification of ROS and transmission of redox signals. In recent years, it has become clear that abiotic stress conditions induce changes in the reduction/oxidation (redox) state of signalling molecules, which in turn modulate gene and protein expression to increase plant acclimation to abiotic stress. This important redox state-related branch of science has given several clues in understanding the adaptive plant responses to different stressful regimes. In this chapter, an overview of the literature is briefly presented in terms of the main function of ascorbate and glutathione in plant cells. Further more, we describe how important forms of abiotic stress regulate the expression of genes and proteins involved in the ascorbate and glutathione redox sensing system.
Keywords: Ascorbate; Glutathione; Redox state; Antioxidant enzymes; Gene expression; Abiotic stress; Reactive oxygen species